Implications of asymptomatic infection for the natural history of selected parasitic tropical diseases - Alvar, Jorge (2020)
Progress has been made in the control or elimination of tropical diseases, with a significant reduction of incidence. However, there is a risk of re-emergence if the factors fueling transmission are not dealt with. Although it is essential to understand these underlying factors for each disease, asymptomatic carriers are a common element that may promote resurgence; their impact in terms of proportion in the population and role in transmission needs to be determined. In this paper, we review the current evidence on whether or not to treat asymptomatic carriers given the relevance of their role in the transmission of a specific disease, the efficacy and toxicity of existing drugs, the Public Health interest, and the benefit at an individual level, for example, in Chagas disease, to prevent irreversible organ damage. In the absence of other control tools such as vaccines, there is a need for safer drugs with good risk/benefit profiles in order to change the paradigm so that it addresses the complete infectious process beyond manifest disease to include treatment of non-symptomatic infected persons.